Fetal Echocardiography in Twin–Twin Transfusion Syndrome - Moon-Grady, Anita J. (American Journal of Perinatology, 2014)
Twin–twin transfusion syndrome is a complex disease process affecting monochorionic twin pregnancies that has implications for the cardiovascular system in both recipient and donor cotwins. Systolic, diastolic, and structural cardiac changes can occur; these have been the subject of intense study over the past two decades, and the use of echocardiography in evaluation of these pregnancies has become common in centers offering treatment of the condition. The role of echocardiography, the clinical cardiovascular and hemodynamic findings characteristic of the syndrome, and proposed pathophysiologic mechanisms and consequences are discussed in this review. Emerging technologies will be presented along with proposed areas for future research.
Keywords: fetal echocardiography; cardiomyopathy; myocardial mechanics